Studies of Connective Tissue Graft Biointegration in Preparing of Tissue Replacing Biomaterials - Manchenko, Anna A.; Mikhailova, Irina P.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2015)
N/A